Efficiency of Fly Ash and Corncob as Alternative Adsorbents for Reducing Fe2+ and Mn2+ in Groundwater - Devitasari, Lucia Adelina; Mohamad Mirwan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Groundwater quality deterioration is common in densely populated areas and industrial zones due to elevated levels of Fe2+ and Mn2+, which alter water's physical properties and pose potential health risks. This study aimed to assess the effectiveness of fly ash and corn cobs as alternative adsorbents for the reduction of Fe2+ and Mn2+ concentrations in groundwater via continuous adsorption processes, with variations in adsorbent bed height and sampling time utilizing 40% H3PO4 as an activator. The results demonstrated that both fly ash and corn cobs were effective, achieving optimum removal efficiencies of 99.7% for Fe²+ and 89.2% for Mn2+ using fly ash, and 99.2% for Fe2+ and 87.7% for Mn2+ using corn cobs. Increasing the height of the adsorbent bed and extending the sampling time improved the removal efficiency of Fe2+ and Mn2+. FTIR analysis confirmed the involvement of –OH, Si–O, C=O, and C–O functional groups in the adsorption process. The Thomas model indicated that Qo decreased while KT increased with increasing adsorbent height. Corn cob exhibited a higher adsorption capacity, whereas fly ash demonstrated faster kinetic rates, with R² values ranging from 0.8052 to 0.9807. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 12: Responsible Consumption and Production